PENGARUH PENGELOLAAN MODAL KERJA DAN RETURN ON EQUITY (ROE) TERHADAP KINERJA KEUANGAN PADA PT. UNILEVER INDONESIA - Alia Nelsa Fitri; Novie Al Muhariah; Hilmi Wiranawata (Ekonomika, 2025)
This study aims to determine the influence of working capital management and Return on Equity (ROE) on the financial performance of PT Unilever Indonesia Tbk. The analytical method used is multiple linear regression with a 5% significance level. Classical assumption tests were also conducted, including normality, multicollinearity, heteroscedasticity, and autocorrelation tests. The type of data used is secondary data obtained from the official website of PT Unilever Indonesia Tbk for the 2019–2023 period. The results show that partially, working capital has a positive effect on financial performance, and ROE has a positive and significant effect on financial performance. Simultaneously, working capital and ROE positively affect the company's financial performance. The coefficient of determination (R Square) is 0.880, indicating that working capital and ROE contribute 88% to the variation in financial performance, while the remaining 12% is influenced by other factors not examined in this study.